2019
DOI: 10.3758/s13415-019-00736-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in reward- and punishment-guided actions

Abstract: Differences in the prevalence and presentation of psychiatric illnesses in men and women suggest that neurobiological sex differences confer vulnerability or resilience in these disorders. Rodent behavioral models are critical for understanding the mechanisms of these differences. Reward processing and punishment avoidance are fundamental dimensions of the symptoms of psychiatric disorders. Here we explored sex differences along these dimensions using multiple and distinct behavioral paradigms. We found no sex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 47 publications
9
42
1
Order By: Relevance
“…In another EEG study of an incentive delay task, boys as compared to girls showed reduced stimulus-preceding negativity when anticipating punishment and greater feedback P3 to monetary than social reward (33). These findings are consistent with a literature of higher female sensitivity to loss, punishment or other negative feedback (27,34,35).…”
Section: Sex Differences In Reward and Punishment Processingsupporting
confidence: 86%
See 2 more Smart Citations
“…In another EEG study of an incentive delay task, boys as compared to girls showed reduced stimulus-preceding negativity when anticipating punishment and greater feedback P3 to monetary than social reward (33). These findings are consistent with a literature of higher female sensitivity to loss, punishment or other negative feedback (27,34,35).…”
Section: Sex Differences In Reward and Punishment Processingsupporting
confidence: 86%
“…A study of multiple rodent behavioral paradigms reported no sex difference in reward-guided associative learning. However, females showed faster punishment-avoidance learning and, after learning, were more sensitive than males to probabilistic punishment but less sensitive when punishment could be avoided with certainty (27).…”
Section: Sex Differences In Reward and Punishment Processingmentioning
confidence: 87%
See 1 more Smart Citation
“…These variables require that study design and data interpretation be informed by known sex differences in key behaviors, and by the broad range of metabolic and motivational states that gonadal hormones modulate in sex-specific ways. These include prominent sex differences in and sex hormone impacts on, sensitivity to positive and negative reinforcement (80)(81)(82)(83)(84)(85)(86)(87)(88). Thus, while there are several options for laboratory testing of ELM in rodents (89)(90)(91)(92)(93), the WWWhen task was selected for its leveraging of rats' innate preference for novelty and spontaneous investigations of novel objects encountered in the environment (63,92).…”
Section: Experimental Design and Data Analyses Minimize Non-mnemonic mentioning
confidence: 99%
“…In practical contexts, rewards are generally weighed with potential negative consequences (7), requiring consideration of the value of a reward and of associated aversive outcomes. Sex-based differences in reward seeking and avoidance -developed over evolutionary history -offer an ideal model to explore bias and strategy in a behavioral task while providing insight into the neurobiological basis of information encoding (8)(9)(10)(11)(12). Previous work has shown that the schedule under which a stimulus is presented is more of a behavioral determinant than the stimulus itself (13,14); while these principles laid the ground-work for behavioral neuroscience, many of these fundamental findings are no longer considered when developing and designing behavioral models in animals.…”
Section: Introductionmentioning
confidence: 99%